Resilience in Reindeer Herders Society - Turi, Ellen Inga (2009)
Turi is an EALAT project Phd student and her Phd will focus on a comparative analysis of resilience in reindeer herding societies using Sami and Nenets reindeer husbandry from Finnmark and Yamal